Evidence of evolution of the black hole mass function with redshift - Rinaldi, Stefano; Pozzo, Walter Del; Mapelli, Michela; Lorenzo-Medina, Ana; Dent, Thomas (Astronomy and astrophysics, 2024)
Aims. We investigate the observed distribution of the joint primary mass, mass ratio, and redshift of astrophysical black holes using the gravitational wave events detected by the LIGO-Virgo-KAGRA collaboration and included in the third gravitational wave transient catalogue Methods. We reconstructed this distribution using Bayesian non-parametric methods, which are data-driven models able to infer arbitrary probability densities under minimal mathematical assumptions. Results. We find evidence that both the primary mass and mass-ratio distribution evolve with redshift: our analysis shows the presence of two distinct subpopulations in the primary mass−redshift plane, with the lighter population, ≲20 M⊙, disappearing at higher redshifts, z > 0.4. The mass-ratio distribution shows no support for symmetric binaries. Conclusions. The observed population of coalescing binary black holes evolves with look-back time, suggesting a trend in metallicity with redshift and/or the presence of multiple redshift-dependent formation channels.